Lactobacillus casei Zhang Counteracts Blood-Milk Barrier Disruption and Moderates the Inflammatory Response in Escherichia coli-Induced Mastitis - Zheng, Yuhui; Liu, Gang; Wang, Wei; Wang, Yajing; Cao, Zhijun; Yang, Hongjian; Li, Shengli (Frontiers in Microbiology, 2021)
Escherichia coli is a common mastitis-causing pathogen that can disrupt the blood-milk barrier of mammals. Although Lactobacillus casei Zhang (LCZ) can alleviate mice mastitis whether it has a prophylactic effect on E. coli-induced mastitis through intramammary infusion, as well as its underlying mechanism, remains unclear. In this study, E. coli-induced injury models of bovine mammary epithelial cells (BMECs) and mice in lactation were used to fill this research gap. In vitro tests of BMECs revealed that LCZ significantly inhibited E. coli adhesion (P < 0.01); reduced cell desmosome damage; increased the expression of the tight junction proteins claudin-1, claudin-4, occludin, and zonula occludens-1 (ZO-1) (P < 0.01); and decreased the expression of the inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 (P < 0.01), thereby increasing trans-epithelial electric resistance (P < 0.01) and attenuating the lactate dehydrogenase release induced by E. coli (P < 0.01). In vivo tests indicated that LCZ significantly reduced the injury and histological score of mice mammary tissues in E. coli-induced mastitis (P < 0.01) by significantly promoting the expression of the tight junction proteins claudin-3, occludin, and ZO-1 (P < 0.01), which ameliorated blood-milk barrier disruption, and decreasing the expression of the inflammatory cytokines (TNF-α, IL-1β, and IL-6) in mice mammary tissue (P < 0.01). Our study suggested that LCZ counteracted the disrupted blood-milk barrier and moderated the inﬂammatory response in E. coli-induced injury models, indicating that LCZ can ameliorate the injury of mammary tissue in mastitis.